AUDIT IN THE CONTEXT OF INFORMATION TECHNOLOGIES: THE ROLE OF DIGITAL AUDIT - Murodova Dilfuza Jalolovna (Web of Journals Publishing, 2025)
This article analyzes the fundamental changes occurring in the field of auditing in the context of digital transformation, focusing particularly on the concept of digital audit, its essence, practical application, and strategic significance. As traditional audit methods no longer meet the requirements of the modern technological environment, auditors are shifting toward tools that operate in real time, rapidly analyze large volumes of data, and leverage artificial intelligence. Using examples from the advanced digital audit systems introduced by the Big Four auditing firms, the paper explores the integration of digital technologies into the audit process, their impact on efficiency metrics, and issues related to cybersecurity. Additionally, the prospects of implementing digital audit in Uzbekistan are examined in depth, considering existing infrastructure, human capital, and the regulatory and legal framework. The findings of the study allow for the evaluation of digital audit as a tool for improving audit systems and enhancing transparency in corporate governance.
Keywords: Digital audit, information technology, artificial intelligence, audit transformation, financial control, audit efficiency, real-time audit, Big Data, audit practice, cybersecurity.